2009
DOI: 10.1128/jcm.00799-09
|View full text |Cite
|
Sign up to set email alerts
|

Novel Clostridium botulinum Toxin Gene Arrangement with Subtype A5 and Partial Subtype B3 Botulinum Neurotoxin Genes

Abstract: ᰔBotulinum neurotoxin, the most poisonous substance known and a potential biothreat agent (1), causes human and animal botulism worldwide (4,9). This toxin is encoded by the bont gene as part of a cluster that includes nontoxic accessory genes (10). Two main gene clusters are known: the hemagglutinincontaining (haϩ) cluster in toxin serotypes A1, B, C, D, and G and the orfX cluster in toxin serotypes A, E, and F (7, 10). In addition, some Clostridium botulinum type A strains (e.g., NCTC2916) contain a silent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
52
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 10 publications
2
52
0
Order By: Relevance
“…1). Recently, a very similar arrangement in a type A5 infant botulism strain (IBCA94-0216) was reported by Dover et al (4). The two type A5 neurotoxin clusters share 99.7% nucleotide sequence identity between the 3Ј end of the cntE (ha70) gene and the 3Ј end of the type B3 neurotoxin-encoding gene.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…1). Recently, a very similar arrangement in a type A5 infant botulism strain (IBCA94-0216) was reported by Dover et al (4). The two type A5 neurotoxin clusters share 99.7% nucleotide sequence identity between the 3Ј end of the cntE (ha70) gene and the 3Ј end of the type B3 neurotoxin-encoding gene.…”
mentioning
confidence: 77%
“…Of 38 other strains of proteolytic C. botulinum also possessing the ha ϩ form of the neurotoxin gene cluster (8), selected as representing a wide range of diseases caused, geographical distribution and type of neurotoxin(s) formed (3), only the type B toxin-forming strain 2345 shared the same deletion, implying that this modification is quite rare. Dover et al (4) suggested that the A5 neurotoxin gene, together with its cntB (ntnh) gene, may have been inserted into a type B neurotoxin cluster. Since microarray analysis showed that strain 2345 clustered with Clostridium sporogenes (3), it is tempting to postulate that a strain of C. sporogenes acquired a type B neurotoxin cluster by horizontal transfer to give a strain similar to strain 2345, which, following a further round of recombination at this locus, gave rise to the type A5 neurotoxin cluster now described.…”
mentioning
confidence: 99%
“…[4][5][6] For example, gene sequence analysis has identified five BoNT/A subtypes (A1 through A5). [7][8][9] Whereas the sequence similarity among different serotypes is relatively low, the subtypes within a BoNT serotype generally exhibit high sequence similarity. The BoNTs are futher divided into toxin variants that are based on minor sequence differences within a toxin subtype derived from different bacterial strains.…”
Section: Introductionmentioning
confidence: 99%
“…Group III encompasses serotype C and D strains, while group IV is only composed of serotype G strains (4,21). Differences in the BoNT gene nucleotide sequences lead to the definition of five subtypes (A1 to A5) for type A, five (proteolytic B1 to B3, bivalent B, and nonproteolytic B) for type B, four (E1 to E3 and E6) for type E, and seven (F1 to F7) for type F (2,3,6,23). Two subtypes from BoNT/E-producing Clostridium butyricum strains (subtypes E4 and E5) have been described (3).…”
mentioning
confidence: 99%